2023
DOI: 10.1093/humupd/dmad011
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and neonatal outcomes after natural versus artificial cycle frozen embryo transfer and the role of luteal phase support: a systematic review and meta-analysis

T R Zaat,
E B Kostova,
P Korsen
et al.

Abstract: BACKGROUND The number of frozen embryo transfers (FET) has increased dramatically over the past decade. Based on current evidence, there is no difference in pregnancy rates when natural cycle FET (NC-FET) is compared to artificial cycle FET (AC-FET) in subfertile women. However, NC-FET seems to be associated with lower risk of adverse obstetric and neonatal outcomes compared with AC-FET cycles. Currently, there is no consensus about whether NC-FET needs to be combined with luteal phase suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…Along those lines, no difference in birthweight was seen by Shi and co-authors when embryos were transferred in a natural cycle, leading one to consider that endometrial preparation might play a crucial relevant role in that regard (Shi et al, 2018). Similar results were also found in a systematic review and meta-analysis performed by Zaat and colleagues (Zaat et al, 2023) including 1,546 studies in which FETs were compared between natural cycles (n = 56,445) and artificial cycles (n = 57,231). The authors reported a decreased risk of adverse obstetric and neonatal outcomes when a natural cycle was adopted compared with artificial treatments.…”
Section: Automated Vitrificationsupporting
confidence: 58%
“…Along those lines, no difference in birthweight was seen by Shi and co-authors when embryos were transferred in a natural cycle, leading one to consider that endometrial preparation might play a crucial relevant role in that regard (Shi et al, 2018). Similar results were also found in a systematic review and meta-analysis performed by Zaat and colleagues (Zaat et al, 2023) including 1,546 studies in which FETs were compared between natural cycles (n = 56,445) and artificial cycles (n = 57,231). The authors reported a decreased risk of adverse obstetric and neonatal outcomes when a natural cycle was adopted compared with artificial treatments.…”
Section: Automated Vitrificationsupporting
confidence: 58%
“…Nevertheless, some studies have evaluated the clinical efficacy of long-acting GnRH agonists in general populations, and have identified a variety of proteins that facilitate embryo implantation in the endometrium, suggesting that long-acting agonists may enhance endometrial receptivity ( 30 ). In addition, another study showed that increased levels of GnRH-a directly modulate the expression of enzymes and cytokines and increase the expression of endometrial tolerance markers such as integrin b3 and leukaemia inhibitory factor, improving endometrial tolerance and clinical outcome in patients with intermediate and very thin endometrium ( 31 ). Xu’s et al ( 23 ) study used clomiphene citrate (CC) + human menopausal gonadotrophin (HMG) protocol for COS.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that AC FET protocol had a higher early pregnancy loss rate than true-NC FET (54.7% versus 33%, P<0.0001) ( 120 ). Similarly, a meta-analysis comparing the obstetric outcomes after NC versus AC FET showed that patients using AC FET protocol had a higher early pregnancy rate ( 121 ). A total of 26 RCTs and 113 cohort studies were included in a network meta-analysis, which compared 7 different FET protocols: true- NC; modified-NC; AC with GnRH agonist suppression; AC without GnRH agonist suppression; aromatase inhibitor (letrozole); clomiphene citrate; and exogenous gonadotropin ( 122 ) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%